The role of estrogen receptor-α and its activation function-1 for growth plate closure in female mice - Börjesson, A. E. (American Physiological Society, 2012)
High estradiol levels in late puberty induce growth plate closure and thereby cessation of growth in humans. In mice, the growth plates do not fuse after sexual maturation, but old mice display reduced longitudinal bone growth and high-dose estradiol treatment induces growth plate closure. Estrogen receptor (ER)-α stimulates gene transcription via two activation functions (AFs), AF-1 and AF-2. To evaluate the role of ERα and its AF-1 for age-dependent reduction in longitudinal bone growth and growth plate closure, female mice with inactivation of ERα (ERα(−/−)) or ERαAF-1 (ERαAF-1(0)) were evaluated. Old (16- to 19-mo-old) female ERα(−/−) mice showed continued substantial longitudinal bone growth, resulting in longer bones (tibia: +8.3%, P < 0.01) associated with increased growth plate height (+18%, P < 0.05) compared with wild-type (WT) mice. In contrast, the longitudinal bone growth ceased in old ERαAF-1(0) mice (tibia: −4.9%, P < 0.01). Importantly, the proximal tibial growth plates were closed in all old ERαAF-1(0) mice while they were open in all WT mice. Growth plate closure was associated with a significantly altered balance between chondrocyte proliferation and apoptosis in the growth plate. In conclusion, old female ERα(−/−) mice display a prolonged and enhanced longitudinal bone growth associated with increased growth plate height, resembling the growth phenotype of patients with inactivating mutations in ERα or aromatase. In contrast, ERαAF-1 deletion results in a hyperactive ERα, altering the chondrocyte proliferation/apoptosis balance, leading to growth plate closure. This suggests that growth plate closure is induced by functions of ERα that do not require AF-1 and that ERαAF-1 opposes growth plate closure.